Language Preference of the Indonesia Economic Subjects' toward Product Labeling - Veronika Listi Ferdini Damopolii (KOMPETENSI, 2022)
The shift of Indonesian Language to Foreign Languages also applies to the labeling of selling products in Indonesia. Economic actors have the choice of maintaining Indonesian language or using foreign language when labeling the product they are going to sell. This study aims to see the language attitude of economic actors towards the products to be marketed. In addition, this study was conducted to see the number of foreign and Indonesian languages used in the country when labeling the products they sell. This research method uses descriptive methods to make descriptions, descriptions, or paintings systematically, factually and accurately. The result obtained is that economic actors prefer to label products in foreign languages rather than Indonesian. From the data found, there are 50 product labels. There are 33 domestic products labeling their products in foreign terms and only 17 domestic products label their products in Indonesian terms.